2019
DOI: 10.1186/s13046-019-1336-3
|View full text |Cite
|
Sign up to set email alerts
|

GKN2 promotes oxidative stress-induced gastric cancer cell apoptosis via the Hsc70 pathway

Abstract: Background The GKN2 is a secretory protein, whose levels decrease in gastric cancer. The present study aimed to investigate the expression, function and mechanism of action of GKN2 in gastric cancer. Methods Molecular biology assays were performed to elucidate the function and underlying mechanisms of GKN2 in gastric cancer under stress-induced condition in vivo and in vitro. Clinical specimens were used to assess the correlation of GKN2 and prognosis. Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 47 publications
0
13
0
Order By: Relevance
“…In a previous study, HSPA8 was found to be important for glioblastoma, and knockdown of HSPA8 interferes with the tumorigenic properties of glioblastoma cells ectopically overexpressing nesting proteins ( 16 ). In gastric cancer, HSPA8 interacts with GKN2 to promote oxidative stress-induced apoptosis, inhibit the NF-κB signaling pathway, and activate the JNK signaling pathway ( 17 ). MAPK9 is a member of the MAP kinase family and acts as an integration point for a variety of biochemical signals involved in various cellular processes such as proliferation, differentiation, transcriptional regulation and development.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study, HSPA8 was found to be important for glioblastoma, and knockdown of HSPA8 interferes with the tumorigenic properties of glioblastoma cells ectopically overexpressing nesting proteins ( 16 ). In gastric cancer, HSPA8 interacts with GKN2 to promote oxidative stress-induced apoptosis, inhibit the NF-κB signaling pathway, and activate the JNK signaling pathway ( 17 ). MAPK9 is a member of the MAP kinase family and acts as an integration point for a variety of biochemical signals involved in various cellular processes such as proliferation, differentiation, transcriptional regulation and development.…”
Section: Discussionmentioning
confidence: 99%
“…Both GKN1 and GKN2 have been identified as novel biomarkers for GC as have been found to be downregulated in GC patients. These genes are involved in the homeostatic regulation of the gastric mucosa (28)(29)(30). Several studies have shown a decrease in levels of GKN1 and GKN2 in gastric tumor tissues and GC cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it has been reported that miR-383 promotes cholangiocarcinoma cell invasion and proliferation by suppressing IRF1 (31). More importantly, in gastric cancer, miR-216a is significantly upregulated (32), and elevation of miR-216a would favor a worse clinical outcome (33). Additionally, elevated miR-216a-3p activates the NF-κB signaling pathway through targeting RUNX1, contributing to metastatic potential of gastric cancer (34).…”
Section: Discussionmentioning
confidence: 99%